2021
DOI: 10.1038/s41598-021-92081-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anti-biofilm effect of poloxamer-based thermoreversible gel of silver nanoparticles as a potential medication for root canal therapy

Abstract: The purpose of this study was to design silver nanoparticles (AgNPs) poloxamer thermoreversible gel (AgNPs-PL) and investigate whether this gel could provide sustained antibacterial activity against Enterococcus faecalis (E. faecalis) in the root canal. The gels fabricated were characterized in terms of gelatin temperature, particle size, in-vitro Ag+ release, and elemental content. Cytotoxicity of AgNPs-PL on primary human periodontal ligament fibroblasts (HPDLFs) was examined by CCK-8 assay. Characterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 73 publications
0
16
0
1
Order By: Relevance
“…For uniform delivery of NCL-EPO-NP on intraoral and intravaginal administration, we incorporated NCL-EPO-NP into our previously reported thermosensitive gel composition containing 20% P407 and 1% Poloxamer 188. We and others have demonstrated that thermosensitive P407 hydrogels can be effectively used for the intraoral and intravaginal application of NPs without affecting their inherent properties and release [ 36 , 37 , 74 , 75 ]. Additionally, we have previously shown that NPs stabilized with P407 show significant enhancement in mucosal transport in vivo leading to improved efficacy [ 57 , 58 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For uniform delivery of NCL-EPO-NP on intraoral and intravaginal administration, we incorporated NCL-EPO-NP into our previously reported thermosensitive gel composition containing 20% P407 and 1% Poloxamer 188. We and others have demonstrated that thermosensitive P407 hydrogels can be effectively used for the intraoral and intravaginal application of NPs without affecting their inherent properties and release [ 36 , 37 , 74 , 75 ]. Additionally, we have previously shown that NPs stabilized with P407 show significant enhancement in mucosal transport in vivo leading to improved efficacy [ 57 , 58 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we have previously shown that NPs stabilized with P407 show significant enhancement in mucosal transport in vivo leading to improved efficacy [ 57 , 58 , 76 ]. Finally, studies have also shown that Poloxamer 407 thermosensitive hydrogel can also interfere with the formation of microbial biofilms [ 75 , 77 , 78 ]. Taken together, usage of mucus-penetrating P407 as a stabilizer for EPO-NCL-NPs and P407 thermosensitive gel to deliver NCL-EPO-NPs was deemed advantageous for improving outcome of in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, studies have also shown that Poloxamer 407 thermosensitive hydrogel can also interfere with the formation of microbial biofilms 76,78,79 . Taken together, usage of mucus-penetrating P407 as a stabilizer for EPO-NCL-NPs and P407 thermosensitive gel to deliver NCL-EPO-NPs was deemed advantageous for improving outcome of in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…For uniform delivery of NCL-EPO-NP on intra-oral and intra-vaginal administration, we incorporated NCL-EPO-NP into our previously reported thermosensitive gel composition containing 20% P407 and 1% Poloxamer 188. We and others have demonstrated that thermosensitive P407 hydrogels can be effectively used for the intra-oral and intra-vaginal application of nanoparticles without affecting their inherent properties and release 36,37,75,76 . Additionally, we have previously shown that nanoparticles stabilized with P407 show significant enhancement in mucosal transport in vivo leading to improved efficacy 58,59,77 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation